2020
DOI: 10.1021/acsomega.0c02154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanobubbles on the Flotation Performance of Oxidized Coal

Abstract: In this study, the effects of air bubbles and nanobubbles on flotation performance and kinetics of oxidized coal were investigated. The surface properties of the coal sample before and after oxidation were characterized by a scanning electron microscope (SEM) and X-ray photoelectron spectroscopy (XPS). The nanobubbles on highly oriented pyrolytic graphite (HOPG) were observed by an atomic force microscope (AFM). The interaction between coal and conventional bubbles in the absence and presence of nanobubbles wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The fact that the curves for NB, NBC, and NBF were always above the conventional bubbles’ curves indicated the improved flotation k . This is consistent with the findings reported in the literature where nanobubbles result in an increased flotation rate constant. From the classical first-order model used (eq ), the correlation coefficients, R 2 , were 0.9958, 0.9989, 0.9853, and 0.9988 for CB, NB, NBC, and NBF, respectively for the −850 μm samples. Whilst the −106 μm samples had R 2 values of 0.9925, 0.9968, 0.9879, and 0.9818 for CB, NB, NBC, and NBF, respectively.…”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The fact that the curves for NB, NBC, and NBF were always above the conventional bubbles’ curves indicated the improved flotation k . This is consistent with the findings reported in the literature where nanobubbles result in an increased flotation rate constant. From the classical first-order model used (eq ), the correlation coefficients, R 2 , were 0.9958, 0.9989, 0.9853, and 0.9988 for CB, NB, NBC, and NBF, respectively for the −850 μm samples. Whilst the −106 μm samples had R 2 values of 0.9925, 0.9968, 0.9879, and 0.9818 for CB, NB, NBC, and NBF, respectively.…”
Section: Results and Discussionsupporting
confidence: 89%
“…Studies have been conducted to assess the influence of bubble sizes generated in various hydrodynamic cavitation systems. ,, Additionally, liquid properties have been addressed, namely, temperature, surfactant type, and dosage. Through the NB generation, an increase in the surfactant concentration has been found to reduce bubble sizes and improve their stability. The change in surface tension explains this as the liquid’s surface tension decreases, and the bubbles formed become finer. , Many NB flotation studies reported improving flotation recoveries, grades, and kinetics and even reduced reagent consumption. , In a recent study, Pourkarimi et al indicated that generation of NBs in the presence of selective collectors could significantly increase the flotation efficiency of fine phosphate ore samples. Surprisingly, surface analyses of flotation concentrates indicated that the amounts of flotation collectors adsorbed onto the surface of floated particles were lower in the presence of NBs than in their absence.…”
Section: Introductionmentioning
confidence: 99%
“…The zeta-potential value depends on the production time-as shown in Figure 7-and a decrease (as an absolute value) with the processing time was found to increase; in this work bulk nanobubbles with oxygen and air were generated in water by counterflow hydrodynamic cavitation. The effects of air bubbles and nanobubbles on flotation performance and kinetics of oxidized coal were studied [72]. It was found that surface nanobubbles were present on highly oriented pyrolytic graphite surface; coal agglomeration occurred in the presence of nanobubbles, indicated by the shear thinning of coal slurry [64,73].…”
Section: Nanobubblesmentioning
confidence: 99%
“…The effects of air bubbles and nanobubbles on flotation performance and kinetics of oxidized coal were studied [72]. It was found that surface nanobubbles were present on highly oriented pyrolytic graphite surface; coal agglomeration occurred in the presence of nanobubbles, indicated by the shear thinning of coal slurry [64,73].…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Compared to the flotation using tap water, the use of NBs alone increased the overall combustible recovery from a baseline of 54.2–67.1% in NB water. The beneficial effect of NBs on coal flotation has been widely acknowledged in the literature. However, after adding PAC to NB water, the ability of NBs to enhance coal flotation was compromised, as suggested by the relatively lower cumulative combustible recoveries in the group of NB water + PAC. A similar decline in combustible recovery using NB water after PAC addition has previously been reported by Li et al, who attributed it to the reduced surface hydrophobicity of coal in the presence of PAC.…”
Section: Resultsmentioning
confidence: 99%